Global Learning Transformation in Primary Education: A Systematic Review of Digital Policy and Access Enhancement - Nisa, Rofiatun; Hadi, Syamsul; Pristiani, Riska (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The digital revolution has encouraged the acceleration of digital transformation in the education sector, including at the elementary school level. This transformation requires policy adaptation to integrate technology effectively into the learning process. This study aims to analyze the literature that puts forward the digital policies implemented in primary schools globally, the impact on increasing access to digital education, and what factors affect the successful implementation of the policy. This article fills a gap in the literature that previously focused on learning outcomes without considering accessibility and equity. This article uses the Systematic Literature Review (SLR) approach using the PRISMA procedure from 2015 to 2024. From various stages of exclusion, 52 articles were found in the Scopus database that followed the inclusion criteria and used the help of the VOSviewer application. The results of the analysis show that global digital policies in primary schools have a significant impact on increasing access to digital education. Approaches such as improved infrastructure, teacher training, and technology-based curricula have improved the quality of learning and reduced the digital divide. Increased access to digital learning has significantly impacted education systems in various countries. Success factors include government policies, technological infrastructure, educator capacity, user acceptance, and socio-economic support.